Translating Culture-Specific Expression in the Balinese Folktale I Juragan Anom: An Analysis of Translation Procedures - Ni Putu Ayu Kartika Sari Dewi; Ni Putu Wulantari; I Made Suamba; Kadek Ayu Kartika Septiana; Ngurah Artha Yoga Pratama (Universitas Pahlawan Tuanku Tambusai, 2026)
Translation involves not only transferring linguistic meaning from the source language to the target language but also conveying the cultural values embedded within a text. Translating culture-specific expressions presents a significant challenge because many cultural concepts lack direct equivalents in the target language, particularly in literary works rooted in local traditions. Despite the growing interest in translation studies, research on culture-specific expressions in Balinese folktales remains limited. Therefore, this study aims to identify the culture-specific expressions found in the Balinese folktale I Juragan Anom and analyze the translation procedures used in rendering them into English. This study employed a descriptive qualitative approach. The data were obtained from Satua Bali: Tales from Bali, compiled by Sutjaja, and analyzed using Newmark’s classification of culture-specific expressions and Vinay and Darbelnet’s translation procedures. The findings revealed four categories of culture-specific expressions: religious culture, customs, material culture, and social culture. Borrowing, literal translation, and adaptation were identified as the primary translation procedures, with borrowing being the most frequently applied. These findings indicate that borrowing effectively preserves the cultural identity and authenticity of Balinese expressions while maintaining their comprehensibility for English readers.